- KEWENANGAN BADAN PENGAWAS PEMILIHAN UMUM DAERAH KABUPATEN TASlKMALAYA DALAM MEMUTUSKAN PELANGGARAN PEMlLlHAN KEPALA DAERAH DI KABUPATEN TASlKMALAYA: - - Yoga Adam Pratama; Wijiningsih, Ninuk (Reformasi Hukum Trisakti, 2023)
Starting with a report Dr. Iwan Saputra, S.E., M.Sc., candidate for Regent of Tasikmalaya Regency, submitted to the Tasikmalaya Regency Bawaslu regarding alleged administrative violations of Article 71  paragraph (3) of Law No. 10 Year 2016, which were allegedly committed by H. Ade Sugianto as the candidate for the incumbent Regent. The Tasikmalaya Regency Bawaslu reviewed the report and issued The issue at hand is whether the Tasikmalaya Regency Bawaslu Number 046/K.Bawaslu.JB-18/PM.00.02/XII/2020 recommendation letter complies with Law Number 10 of 2016 or not. Does Tasikmalaya Regency KPU Decision Number 531/PY.02.1-BA/3206/KAB/I/2021 follow the advice of the Tasikmalaya Regency Bawaslu? The deductive technique is used to draw conclusions in the normative juridical research method, which is a descriptive-analytical approach. The findings of the study and discussion demonstrate that the Tasikmalaya Regency Bawaslu Number 046/K.Bawaslu.JB-18/PM.00.02/XII/2020 recommendation letter violated authority in terms of time (onbevoegdheid ratione temporis), which is contrary to Article 5 of Law Number 1 of 2015. The recommendations made by Bawaslu are not in compliance with processes (formal faults) for handling election administration infractions, therefore the Tasikmalaya Regency KPU letter Number 531/PY.02.1-BA/3206/KAB/I/2021 conforms with legal requirements.